Quṣayr ʻAmra : art and the Umayyad elite in late antique Syria - Fowden, Garth (Berkeley, Calif. : University of California Press, 2004)
The remarkable frescoes of Quṣayr ʻAmra were probably painted in the middle of the 8th century for a Muslim Arab prince. However many problems remain with regard to the date, the patron & even the meaning of the often erotic scenes. Garth Fowden explores this treasure from the Syrian Desert.
Musil's Fairy-Tale Castle -- Luxuries of the Bath -- The Hunt -- "O God, Bless the Amír" -- The Princely Patron -- Maintaining the Dynasty -- The Six Kings -- A Captive Sasanian Princess -- Qusayr 'Amra Contextualized -- Umayyad Self-Representation.
Includes bibliographical references (pages 335-374) and index.
Print version record.
English.
JSTOR
Keywords: Qusayr ʻAmrah (Jordan : Dwelling); Quṣayr ʻAmra (Jordanie); Qusayr ʻAmrah (Jordan : Dwelling); Mural painting and decoration, Umayyad -- Jordan -- Foreign influences; Arabic poetry -- 622-750 -- History and criticism; Poésie arabe -- 622-750 -- Histoire et critique; ART -- Graffiti & Street Art; HISTORY -- Ancient -- General; Arabic poetry; Jordan; 622 - 750; Humaniora -- Kunst; Criticism, interpretation, etc